Strategi Fundraising dalam Meningkatkan Dana ZIS di LAZ PERSADA Jawa Timur - Latifatussufiah Latifatussufiah; Mohammad Fathan Syarief; Muhammad Saiful Afriyanto; Lian Fuad (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims at Fundraising Strategy in Increasing ZIS Funds in LAZ PERSADA East Java. One of the most important things in a zakat institution is fund raising activities. Fundraising is an activity to collect funds and other resources from the community, whether individually, in groups or organizations, where the funds will be distributed and utilized for the benefit of the mustahik. So in this case, zakat institutions must have an efficient and effective fundraising strategy so that these funds can be managed optimally. LAZ PERSADA is one of the amil zakat institutions that has succeeded in raising tens of billions of funds over the last two years, this cannot be separated from the fundraising strategy they have. This research uses descriptive qualitative research methods and data sources come from interviews and documentation. The results of this research show that the fundraising strategy implemented by LAZ Persada is broadly grouped into three, namely retail or direct collection, partnerships such as corporate social responsibility, and digital channels or indirect collection such as websites and social media.